2003
DOI: 10.1073/pnas.0337481100
|View full text |Cite
|
Sign up to set email alerts
|

Course of illness, hippocampal function, and hippocampal volume in major depression

Abstract: Studies have examined hippocampal function and volume in depressed subjects, but none have systematically compared nevertreated first-episode patients with those who have had multiple episodes. We sought to compare hippocampal function, as assessed by performance on hippocampal-dependent recollection memory tests, and hippocampal volumes, as measured in a 1.5-T magnetic resonance imager, in depressed subjects experiencing a postpubertal onset of depression. Twenty never-treated depressed subjects in a first ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
466
8
23

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 861 publications
(527 citation statements)
references
References 46 publications
30
466
8
23
Order By: Relevance
“…This contrast between suicide groups is consistent with the prominent role of the highly plastic hippocampus in depression and stress response, 20,54 discriminating between depressive and non-depressive states for a subset of differentially expressed genes. A gene ontology analysis of probes that were significantly differentially expressed between the two suicide groups in the hippocampus reveals a strong overrepresentation of factors involved in transcriptional regulation and metabolism, similar to the result including all comparisons in the hippocampus, but with a much higher degree of significance.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This contrast between suicide groups is consistent with the prominent role of the highly plastic hippocampus in depression and stress response, 20,54 discriminating between depressive and non-depressive states for a subset of differentially expressed genes. A gene ontology analysis of probes that were significantly differentially expressed between the two suicide groups in the hippocampus reveals a strong overrepresentation of factors involved in transcriptional regulation and metabolism, similar to the result including all comparisons in the hippocampus, but with a much higher degree of significance.…”
Section: Discussionsupporting
confidence: 78%
“…In the amygdala, alterations in cerebral blood flow and metabolism, 6 asymmetry of amygdalar volumes, 7 as well as smaller [8][9][10] and larger volumes [11][12][13][14] have been observed in depressed subjects when compared with normal controls. In the hippocampus, volumetric analysis studies have also revealed reduced volumes in subjects suffering from major depression in some, 7,11,[14][15][16][17][18][19][20] but not all studies 10,[21][22][23] comparing depressed patients versus controls. Alterations in the cingulate cortex have also been observed by many authors.…”
Section: Introductionmentioning
confidence: 99%
“…At one time state-of-the-art MRI incorporated contiguous 5 mm thick slices; 56 however, lately contiguous slices of 1.5 mm or less are commonly used. 57,58 Thus, although Watson et al 20 used 3 mm thick slices, later studies performed by this research group 59,60 report using slice thicknesses of 1.5 mm.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…47-48 Some of the processes with presumed etiological roles could be subsumed under the vascular or inflammatory hypotheses, but others such as amyloid plaque formation 49-50 are unique to this hypothesis. Interestingly, hippocampal regions have been found to be especially vulnerable to ischemia 51 and to activation of the hypothalamic-pituitary-adrenal (HPA) axis, resulting from stress and chronic medical illness. 52 This latter observation may be of particular relevance to the etiology of LLD relative to early-onset depression, given the well-known role of stress and HPA axis dysfunction (i.e., glucocorticoid hypersecretion) on neurotoxicity of the hippocampus and the increased length and probability of exposure to stress with advancing age.…”
Section: Current Hypotheses For Biological Mechanisms Promoting Lldmentioning
confidence: 99%